RETRACTED Emerging Trends and Research Hotspots in Digital Public Spaces: A Bibliometric Analysis Using VOSviewer - Aguspriyanti, Carissa Dinar (EMARA: Indonesian Journal of Architecture, 2025)
This article has been retracted following the author's request, which was submitted shortly after the original publication but experienced significant processing delays due to internal editorial communication challenges. The author identified post-publication concerns requiring substantial revisions that would fundamentally alter the core findings, and given the extended timeline between the initial retraction request and editorial response, full retraction was determined to be the most appropriate resolution. The editorial board's investigation confirmed no evidence of research misconduct, data fabrication, plagiarism, or ethical violations, and we have since implemented improved protocols to ensure timely processing of author requests. This retraction reflects both the author's commitment to research integrity and our commitment to transparent editorial practices. The dataset selection criteria and temporal parameters require substantial revision that would fundamentally alter the core findings. The editorial board conducted a thorough review and found no evidence of research misconduct, data fabrication, plagiarism, or ethical violations. This is a voluntary, author-initiated retraction based on post-publication methodological assessment.The editorial board acknowledges a delay in processing this request due to internal communication challenges. The author submitted the retraction request promptly after publication, demonstrating immediate awareness and commitment to research integrity. We have implemented improved protocols to ensure timely responses to such requests.This retraction reflects the self-correcting nature of scholarly research and the shared commitment to maintaining only methodologically sound research in the permanent record.